Intersezioni: classico e cristiano nel centone biblico di Proba - Paola Francesca Moretti (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
Proba is a 4th century poetess who belonged to the Roman aristocratic family of the Petroni Probi. A very well-educated woman, she reworked Vergil’s hexameters and hemistichs into a biblical cento (approximately 600 verses), starting from the creation of the world and ending with Christ’s Ascension to Heaven. This work was read by and had a deep infl uence on Empress Eudocia, who after Proba composed a Homeric Christian cento in Greek. Proba’s Cento refl ects the scholastic techniques of memorizing and interpreting ancient poetry, especially Vergil, who, although a pagan, is treated as a pivotal author throughout Antiquity, even by Christians. Some scholars suggested that Proba, as a Christian, did intend her poem to replace the reading of Vergil at grammarian schools, by “cleaning” and Christianising his work. However, a close look shows that Proba was skillfully using Vergilian fragments to interpret the biblical episodes which she was retelling. For example, God’s love towards His creatures and Peter’s love towards (dead) Christ are described by quoting words referred by Vergil to Dido’s love for Aeneas, whereas Christ’s injured and wounded body, when he appears to the disciples after resurrection, is “commented upon” by quoting the unjust and cruel deaths of Sichaeus and Deiphobus. As a result, we should think of Proba’s expected reader as being familiar with Vergil’s hypotext quite well; otherwise, he or she would not be able to grasp the Christian meaning of the Cento. Moreover, the Cento’s episode of the Last Supper is analysed in detail. Here, two passages from the 5th book of the Aeneid serve as“Leitreminiszenzen”: ludi funebres in honour of Anchises, and Palinurus’ death. This analysis shows that even those lines that might seem mere mosaics made up of “neutralised” Vergilian tesserae can disclose their treasures if one comprehends them properly. Vergil is defi nitely being made to speak pia munera Christi (Proba 23) to such extent that some of Vergil’s words used by Proba cannot be understood properly unless we reinterpret them in light of their meaning in the Christian Sondersprache. This shows that Proba’s being a Christian is connected inextricably to her being Vergilian, and that her Cento is a goldmine that hides treasures, many of which are still waiting to be dug out.